Badanie preferencji wobec produktu turystycznego wsi - Woźniak, Marian (Preference Research to the Country Tourist Product, 2006)
The article presents landscape of rural areas as an important element of tourist product. The quality of landscape is more and more often interpreted (which is confirmed by scientific research) as the basic factor influencing choice of a particular place of rest. Tourists staying on rural areas search mainly for: beautiful sceneries, interesting nature, silence and quietness, original agricultural landscapes and attractive cultural heritage. To reach the next level the agritourism needs proper analysis and development as well as larger usage of information from marketing research in shaping quality of tourist product of rural areas.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 447-453